A debtor world interdisciplinary perspectives on debt - Brubaker, Ralph; Lawless, Robert M., 1964-; Tabb, Charles Jordan (New York ; Oxford : Oxford University Press, 2013)
The goal of this collection is to explore debt neither as a problem nor a solution but as a phenomenon and to promote the exchange of knowledge to better comprehend why consumers and businesses decide to borrow money. It asks what happens to businesses and consumers under a heavy debt load, and what legal norms and institutions societies need to encourage the efficient use of debt while promoting a greater understanding of the global phenomenon of increased indebtedness and societal dependence.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Includes index.
Keywords: Debtor and creditor -- England; Bankruptcy -- England; Debtor and creditor; Bankruptcy